Policing gentrification or policing displacement? Testing the relationship between order maintenance policing and neighbourhood change in Los Angeles. (February 2022) - Collins, Charles R.; Stuart, Forrest; Janulis, Patrick
Urban scholars increasingly contend that local police departments play a central role in facilitating neighbourhood change. Recent critics warn that 'order maintenance' policing and other low-level law enforcement tactics are deployed in gentrifying areas to displace 'disorderly' populations. Despite influential qualitative case studies, there remains scant quantitative research testing this relationship, and few studies that evaluate the link between policing, displacement and gentrification. We address this lacuna, drawing on new citation data from the Los Angeles Police Department (LAPD) and employing a measure of neighbourhood change that focuses on the displacement of low-income residents. Examining policing patterns in 978 US Census tracts in Los Angeles over four years, our analysis reveals that tracts experiencing gentrification – defined as the simultaneous increase in non-poor residents and decrease in the number of people in poverty – experience a greater number of citations compared with other tract types. Similar patterns emerge in our analysis of citations that explicitly target homelessness and extreme poverty. In post-hoc analyses, we found that Census tracts characterised by a decrease in the number of people in poverty experienced greater numbers of total police citations and of citations targeting homeless individuals, compared with other tract types. These findings carry important theoretical implications for understanding the divergent manifestations of, and potential mechanisms driving, order maintenance policing. Methodologically, we contend that police citations provide a more precise measure of order maintenance policing compared with previous studies, and that classifying neighbourhoods in terms of relative displacement of residents in poverty provides much-needed interpretive clarity.